Relation between serum myokines and phase II cardiac rehabilitation. Issue 16 (April 2017) - Han, Der-Sheng; Hsiao, Ming-Yen; Wang, Tyng-Guey; Chen, Ssu-Yuan; Yang, Wei-Shiung
Abstract : Abstract: Patients with coronary heart disease or acute myocardial infarction after cardiac catheterization with stenting referred for phase II cardiac rehabilitation (CR) were grouped according to their preference. Cardio-pulmonary exercise testing (CPET) was used to determine oxygen uptake ( ) at peak exercise and anaerobic threshold (AT). The control patients received counseling only while the experiment group received 36 sessions of CR in 3 to 6 months. Exercise physiology parameters and serum myokines (myostatin, insulin-like growth factor-1 (IGF-1), and interleukin-6 (IL-6) were measured pre- and postrehabilitation. There were 29 patients in the experiment group and 10 in the control group, with no significant differences in baseline parameters. The experiment group had prominent progress in aerobic capacity and body composition after CR, but their serum myokine concentrations did not change significantly. Serum myostatin is positively correlated to peak pre- and post-training, and pretraining AT, after adjusting for age, sex, and body composition. Serum IGF-1 is positively correlated with grip strength before training. Serum myostatin level is positively correlated to aerobic capacity, and IGF-1 level is positively correlated to grip strength in cardiac patients receiving CR. Abstract : Supplemental Digital Content is available in the text